Amplification of Artificial Intelligence in 2024 Election News in Online Media in Indonesia - Stefanny Tirza Kurniawan (Pt. Anagata Sembagi Education, 2024)
This research discusses framing carried out by online media, Detik.com, which conveys the potential use of artificial intelligence (AI) and its impact in elections. The massive involvement of artificial intelligence (AI) in people's daily lives opens up great opportunities for the involvement of artificial intelligence (AI) as an efficient and effective campaign suggestion. This research aims to investigate the framing carried out by Detik.com in an article entitled